Senescence in cells of the aging and degenerating intervertebral disc: immunolocalization of senescence-associated beta-galactosidase in human and sand rat discs - Gruber, Helen E; Ingram, Jane A; Norton, H James; Hanley, Jr, Edward N (Spine (Philadelphia, Pa. 1976), 2007)
Human intervertebral disc anulus tissue was obtained in a prospective study of cell senescence. Localization of the senescence biomarker beta-galactosidase (senescence associated beta-galactosidase, SA-beta-gal) was used for quantitative determination of the % senescent cells. Discs were obtained from surgical specimens or control donors. Discs were also studied from the lumbar spine of the sand rat. Experimental studies were approved by the authors' Human Subjects Institutional Review Board and animal use committee. To determine the incidence of cell senescence in human discs with Thompson Grades I through V using immunocytochemistry to quantify the percentage of cells positive for the senescence biomarker SA-beta-gal. Cell senescence has been recognized as a potential factor playing a role age-related disc degeneration. Senescent cells are viable but have lost the ability to divide. Senescence cells, however, are metabolically active. Fifty-seven discs specimens from 54 subjects were examined with immunocytochemistry for anti-SA-beta-gal immunocytochemical localization to identify senescent cells. The fraction of positive cells was determined with quantitative histomorphometry. Quantitative histomorphometry of human discs show an overall incidence of SA-beta-gal-positive cells of 29.9% (+/-24.8, SD), with a range from 0 to 92.01%. Analysis by ANOVA of the % senescent cells grouped by Thompson grade showed significant increases in senescence with increasing disc degeneration (P < 0.0001). Further analysis with Tukey's test showed significant differences between the % senescent cells in Grades I/II versus IV, and versus V. SA-beta-gal-positive cells were also present in discs of the aging sand rat spine. Quantitative analysis of immunohistochemical localization of SA-beta-gal identified a sizeable population of senescent cells in the aging/degenerating disc. It is important to discover more about the senescent disc cell population because these cells persist and accumulate over time within the disc. Since senescent cells cannot divide, senescence may reduce the disc's ability to generate new cells to replace existing ones lost to necrosis or apoptosis.